Pengaruh Kemudahan Akses dan Persepsi Keamanan terhadap Keputusan Penggunaan GoPay: Peran Moderasi Manajemen Fintech pada UMKM Kota Semarang - Didik Sofyan Haryadi; Ronaldo Aprili; Aldina Esty Purwanti; Kapsah Kapsah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This research was designed to explore how perceived security and ease of access shape GoPay adoption choices among MSMEs in Semarang, with a specific focus on the moderating role of fintech management. Methodologically, the study employed a quantitative associative design. Data was collected via a 5-point Likert questionnaire from 100 purposively sampled MSME operators and processed using PLS-SEM through SmartPLS. The results highlight that ease of access, perceived security, and fintech management each exert a significant, positive impact on the decision to use GoPay, collectively yielding an Adjusted R Square of 0.827. However, the data revealed an interesting dynamic: fintech management did not actually moderate the effects of ease of access or security. Rather than strengthening those relationships, it operates as a direct catalyst for usage. Theoretically, this confirms that the Technology Acceptance Model remains a solid framework for understanding fintech adoption among small businesses. From a practical standpoint, the message to fintech companies is straightforward. To ensure long-term, sustainable usage, they cannot just rely on a seamless interface or tight security; they must integrate solid service management into their overall strategy.